Targeting cytokine and chemokine signaling pathways for enhancing chemo-sensitivity in colorectal cancer - Shisen Li; Mianjiao Xie; Yongtao Du; Zhaobang Tan (Cell Communication and Signaling)
Abstract Chemo-resistance is one of the main obstacles in the treatment of colorectal cancer. Many studies have been performed to identify the mechanisms associated with chemo-resistance in colorectal cancer cells, and it has been found that increasing the activity of ABC family transporters, enhancing DNA repair, weakening apoptosis, strengthening stemness, and EMT are among the most important of these mechanisms. Inflammation and cytokines have been linked to colorectal cancer, and there is even a type of colorectal cancer that is caused by chronic inflammation in patients with inflammatory bowel disease. However, the association between cytokines and chemo-resistance in colorectal cancer cells is not yet clear. Various studies have shown that chemotherapy drugs, by affecting the tumor microenvironment, can enhance the recruitment of some immune cells and the production of some cytokines. These cytokines have a variety of effects on various chemo-resistance mechanisms in colorectal cancer cells. Some of them can strengthen chemo-resistance and others weaken chemo-resistance. IL-6, TNFα, IFN, IL1, IL8, IL-17, IL-10, and IL-22 are among the most important cytokines whose effects on chemo-resistance mechanisms in colorectal cancer cells are known. In this article, we will have a comprehensive overview of the effects of these cytokines on chemo-resistance mechanisms in colorectal cancer cells.